Disnep: winnie the pooh: playing games - Kurtz, John (Scholastic Australia Gosford, NSW, 2021)
"Winnie the Pooh: Playing Games" is a charming collection of playful adventures featuring Pooh and his friends from the Hundred Acre Wood. In this delightful book, the beloved characters engage in a variety of fun games, from hide-and-seek to treasure hunts. Through laughter and teamwork, they discover the importance of friendship and sharing. With vibrant illustrations and simple text, this book invites young readers to join Pooh and his pals in celebrating the joy of play, making it a perfect read for storytime or cozy moments.